2021
DOI: 10.7554/elife.60095
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral natural killer cells in chronic hepatitis B patients display multiple molecular features of T cell exhaustion

Abstract: Antiviral effectors such as Natural Killer (NK) cells have impaired functions in chronic hepatitis B (CHB) patients. The molecular mechanism responsible for this dysfunction remains poorly characterized. We show that decreased cytokine production capacity of peripheral NK cells from CHB patients was associated with reduced expression of NKp30 and CD16, and defective mTOR pathway activity. Transcriptome analysis of patients NK cells revealed an enrichment for transcripts expressed in exhausted T cells suggestin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…Hepatitis B infection alters the surface receptor expression and activation status of innate and adaptive immune cells. During CHB, NK cells display higher expression of inhibitory receptor NKG2A, while activation receptors CD16 and NKp30 were downregulated [ 58 , 59 ]. These changes are associated with serum HBV DNA load.…”
Section: Innate and Adaptive Immune Response Against Hbv Infectionmentioning
confidence: 99%
“…Hepatitis B infection alters the surface receptor expression and activation status of innate and adaptive immune cells. During CHB, NK cells display higher expression of inhibitory receptor NKG2A, while activation receptors CD16 and NKp30 were downregulated [ 58 , 59 ]. These changes are associated with serum HBV DNA load.…”
Section: Innate and Adaptive Immune Response Against Hbv Infectionmentioning
confidence: 99%
“…[7,82] Similar observations were made in NK cells, both in mouse and human, during cancer or chronic infections. [83][84][85][86] How this unbalance contributes to the exhausted phenotype is not entirely clear. As reviewed here, T-bet is important to promote terminal maturation and blood circulation, to preserve viability, and to sustain responsiveness to IL-12 and other cytokines.…”
Section: Loss Of T-bet and Maintenance Of Eomes In Exhausted T And Nk...mentioning
confidence: 99%
“…In patients with chronic HBV and HCV infection, low frequencies of circulating NK cells combined with diminished production of proinflammatory cytokines, TNF-α, and IFN-γ have been reported as compared to healthy controls [11,12]. Nevertheless, controversy exists regarding the impact of chronic viral infection on NK cell cytolytic function; while several researchers reported impaired NK cytotoxicity, other reports showed that effector function was not changed [17,18]. The differences in outcomes between these studies were probably due to the lack of standardized protocol and reagents, as well as the heterogeneity of patients.…”
Section: Nk Cells In Chronic Viral Hepatitismentioning
confidence: 99%
“…Therefore, targeting TGF-β appears to represent an intervention strategy to boost NK cell mediated tumor immunity and should be considered in future cancer treatment modalities. The importance of NK cells and their activating receptor/ligand axis in HCC immune surveillance has been extensively of 18 studied and patients with decreased expression of major histocompatibility complex class I chain-related protein A (MICA) in HCC tissue showed reduced disease-free and overall survival compared with patients with preserved MICA expression [78]. Innate lymphoid cell (ILC-1) or liver-resident NK cells play versatile roles in liver diseases.…”
Section: Nk Cells and Immune Surveillancementioning
confidence: 99%